A theoretical approach for zone‐based management of the deer population on Yakushima Island. Issue 2 (1st March 2016) - Fujimaki, Aomi; Shioya, Katsunori; Tagawa, Satoshi; Matsuda, Hiroyuki
Abstract: The biological balance of Yakushima Island is currently being compromised by overpopulation of sika deer ( Cervus nippon yakushimae ). We predicted that the island's deer population would continue to grow unless control efforts are raised threefold from their 2012 levels. To identify the best management practice for future implementation, we evaluated and compared the performances of three different zone‐based management strategies. Under the current management scenario, the median population size of the sika deer on the island would temporarily decrease, but it would subsequently rebound. Under a scenario that allows management zones to be prioritized according to the occurrence of threatened plant species and deer population size, model simulations suggested that the scenario focusing on the central zone would show the best performance based on the probability of achievement of the management goal (assuming that there is no dispersal between zones). This course of action would lead to a decrease in the median deer population size and would further ensure a high probability of achieving the 2022 target population size across most zones (up to 85 %), even if catch levels were not increased. In a future study, we would need to conduct a more detailed analysis of plants and deer density distributions.